(untitled) (Mustansiria Dental Journal, 2019)
Background: Obesity and periodontal disease are diseases of multifactorial etiology closely related to dietary habits and sociodemographic background of the individuals. The aim of this study was the assessment of selected salivary antioxidants and gingival health condition among a group of obese females aged 20-22 years in comparison with normal weight females. Materials and methods: The study group included 40 obese females, with an age range 20-22 years old. The control group included 40 normal weight females of the same age. Body weight was assessed by using the Body Mass Index (BMI). Collection of unstimulated salivary samples was carried out under standardized conditions. Plaque and gingival indices were used for recording the oral hygiene and gingivitis. Salivary flow rate was measured then salivary samples were analyzed to determine the concentration of salivary antioxidants (total protein and uric acid). Results: The data analysis of the present study found that the level of salivary total protein was lower among the obese females compared to the normal weight females with statistically highly significant difference (p<0.01), while salivary uric acid was statistically highly significantly higher among the obese than the normal weight females (p<0.01). Salivary analysis demonstrated that the salivary flow rate was statistically highly significantly higher among the obese females (p<0.01). The mean values of plaque index and gingival index were lower among obese females compared to the normal weight females with statistically highly significant difference for plaque index (p<0.01). Conclusions: The result of this research revealed that salivary antioxidant (uric acid) and salivary flow rate were higher among obese females than normal weight females which may play a role in protection oral tissue from oral diseases in addition to the oral cleanliness effect.